Enhancing Tax Compliance in Malaysia: Does Tax Learning and Education Matter? - Abu Hassan, Norul Syuhada; Palil, Mohd Rizal; Ramli, Rosiati; Maelah, Ruhanita (International Business Education Journal, 2022)
The self-assessment system has become the key administrative approach for personal and corporate taxation in developed and developing countries, including Malaysia, first implemented in 2001 for companies, followed by individual taxpayers in 2004. It is one of the most significant transformations in Malaysia’s taxation, which requires higher tax awareness and improvements in voluntary tax compliance, especially for individual taxpayers. The present paper attempts to uncover the role of compliance strategies in increasing tax compliance and reveal the importance of tax learning and education, one of the central focuses of the tax authority in Malaysia. The study examines three Inland Revenue Board Malaysia’s (IRBM) current strategies: the threat of punishment, tax learning and education, and interaction with the tax authority. From a survey of 501 respondents, the results suggest that IRBM’s two current strategies (threat of punishment and tax learning and education) have a significant positive relationship with tax compliance behaviour among individual taxpayers. In addition, this study proposed enhancing tax learning and education by using current technology in delivering tax knowledge efficiently and embedding tax syllabus in schools and universities. The findings of this study provide significant and valuable input to the tax authorities, particularly IRBM, in evaluating current compliance strategies with the mission to cultivate tax compliance behaviour.